Digital Transformation Adoption Challenges: IT Industry in India - Kushwaha, Devanshu (Global journal of Business and Integral Security, 2024)
In today's dynamic business landscape, digital transformation is imperative for modern businesses' sustained success and competitiveness. The rapid evolution of technology, especially within the IT industry, presents unique challenges to seamlessly adopting digital technologies. This research proposal seeks to comprehensively explore and analyze the hurdles hindering the adoption of digital transformation in the Indian IT industry and, crucially, propose practical solutions to overcome these challenges. A mixed-method approach to this research combines qualitative insights from interviews with IT professionals, and quantitative data gathered through a survey of employees from IT organizations and focused social media, ensuring a comprehensive understanding. The focus is on understanding the psychological factors and leadership roles that often challenge successful digital transformation initiatives within the Indian IT context. By examining these complexities, the study aims to provide detailed insights into diverse organizations' specific obstacles and present strategies to navigate and surmount these challenges. Key questions addressed by the research include: (1) How do individual psychological factors shape the adoption and acceptance of new technologies within an organization? (2) What is the relation between leadership roles and the successful implementation of technological transformations? (3) How do group dynamics and organizational culture jointly influence the adoption of new technologies? (4) What strategies can leaders deploy to cultivate a supportive environment for technological transformation while effectively addressing psychological challenges? Anticipated outcomes encompass identifying primary challenges confronted by IT industries in India while adopting digital transformation. The research will conclude by developing a robust framework to guide enterprises in overcoming these challenges, coupled with actionable recommendations for successfully implementing digital transformation initiatives. This research aspires to contribute valuable insights that not only illuminate the specific challenges within the IT industry in India but also offer practical solutions. By doing so, it aims to serve as a guiding resource for fostering a culture of successful digital transformation adoption in the dynamic landscape of the Indian IT sector.